PENGARUH KUALITAS PENDIDIKAN TERHADAP KEPUASAN MAHASISWA LULUSAN PRODI DIII KEBIDANAN DI STIKes RESPATI TASIKMALAYA - Annisa Rahmidini; Firman F. Wirakusumah; Sari Puspa Dewi (CR JOURNAL (CREATIVE RESEARCH FOR WEST JAVA DEVELOPMENT), 2015)
The high level of competition among educational institutions demands each institution to be able to manage itsinstitution professionally. Educational institution could address high competitiveness by having a good qualityeducation. The decision of an institution to conduct a systematic quality improvement action serves asdeterminant to handle students’ complaints so that at the end, it can increase the satisfaction of graduates. Thepurpose of this study is to analyze the influence of quality of education (governance, community service,curriculum study, learning process, human resources, academic atmosphere, research and publications,student affairs, finance, as well as infrastructure and facilities) towards satisfaction of graduates in RespatiHealth Science Institute (STIKes) Tasikmalaya. The method used is quantitative research with cross sectionalstudy design. The population in this study is all graduates of STIKes Respati Tasikmalaya in the past two years,namely Batch VII and VIII amounting to 201 graduates. Sampling techniques taken in this study is simple randomsampling in total of 106 graduates. Methods of data collected in this study through questionnaire. The resultsshow that there is a positive influence between qualities of education towards satisfaction of graduates in STIKesRespati Tasikmalaya. It is expected that STIKes Respati Tasikmalaya improves the quality of education so thatgraduates can be satisfied.